Finite Element-Based Evaluation of Double-Hull Midsection Performance under Oblique Collision - Malsyage, Dina; Bahatmaka, Aldias; Kirana, Arnova Chandra Cahya; Won, Lee Sang; Hee, Song Yeon (Mekanika: Majalah Ilmiah Mekanika, 2025)
Ship collisions pose a significant concern in maritime safety, particularly for double hull vessels operating in confined or high-risk areas. Understanding the structural response to collision is essential for improving crashworthiness. This study investigates the safety limits of a double-hull midsection ship under oblique impacts. Finite Element Analysis (FEA) was used to simulate three collision angles (45°, 60°, 90°) and four velocities (1, 3, 5, and 7 m/s). A benchmark study confirmed simulation accuracy with an error of less than 2%. The study reveals that impact angle and velocity significantly affect the ship's structural response. Perpendicular impacts (90°) with varying velocities produce the highest internal energy, reaching up to 28.99 MJ. In oblique impacts at 45°, the highest crushing force was generated, which reached 51.05 MN. Safety factor analysis indicates that impacts exceeding 3 m/s, especially those approaching perpendicular, lead to a decrease in structural integrity, falling below the acceptable limit. At 7 m/s and 90°, the stress on the inner hull exceeds the material's ultimate strength, indicating a potential for failure. To ensure structural safety, operational speeds should be limited to below 3 m/s. Findings highlight the importance of managing collision risks and guiding future ship design optimization.